2017
DOI: 10.4103/1735-3327.201140
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of substance P and neurokinin A in gingival crevicular fluid of healthy and painful carious permanent teeth

Abstract: Background:It is shown that neuropeptides can be transported from pulp chamber to periodontal ligament through apical foramen and accessory canals. Therefore, clinical pulpal pain leads to expression of preinflammatory neuropeptides such as substance P (SP) and neurokinin A (NKA) in gingival crevicular fluid (GCF). This study aimed to evaluate levels of SP and NKA in GCF of carious and healthy permanent teeth, comparatively.Materials and Methods:This cross-sectional study was performed on twenty children refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several other studies suggest that SP/NK-1R has a definitive role in inflammatory processes. This was confirmed due to considerably higher SP/NK-1R expression in the inflamed pulp [ 21 , 22 ]. One study reported an 8-fold increase in levels of SP, and it was eminent in pulpal tissue clinically diagnosed with irreversible pulpitis versus that of clinically healthy pulp tissue [ 22 ].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several other studies suggest that SP/NK-1R has a definitive role in inflammatory processes. This was confirmed due to considerably higher SP/NK-1R expression in the inflamed pulp [ 21 , 22 ]. One study reported an 8-fold increase in levels of SP, and it was eminent in pulpal tissue clinically diagnosed with irreversible pulpitis versus that of clinically healthy pulp tissue [ 22 ].…”
Section: Discussionmentioning
confidence: 81%
“…This was confirmed due to considerably higher SP/NK-1R expression in the inflamed pulp [ 21 , 22 ]. One study reported an 8-fold increase in levels of SP, and it was eminent in pulpal tissue clinically diagnosed with irreversible pulpitis versus that of clinically healthy pulp tissue [ 22 ]. Consequently, irreversible pulpitis is associated with momentous instigation of this peptidergic system but there is lack of sufficient data related to expression of NK-1R in human dental pulp during inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…Heidari et al . [ 15 ] conducted a cross-sectional study to evaluate the levels of SP, and NKA in GCF of painful human teeth and compared the levels to healthy teeth. Children diagnosed with SIP ( n = 20) in the permanent first molar were screened through the strict inclusion and exclusion criteria and were to subjected to GCF sampling where a gamma-sterilized paper number 30 was used.…”
Section: R Esultsmentioning
confidence: 99%
“…NKA binds to NK1R, initiating an inflammatory process through the NF-kB signaling in macrophage/monocyte cells; whereas the neurological functions of NKA are primarily mediated by NK2R (84). (35,48). Although SP and NKA are also upregulated in GCF of teeth with periodontitis, the levels are reduced after periodontal treatment (85).…”
Section: Neurokinin Amentioning
confidence: 99%